Optimization of ohmic heating of whey based drink using response surface methodology - Amitabh, Anupam; Kumar, Vishal (Journal of Postharvest Technology, 2017)
Experiments were conducted according to Box Behnken Design for optimization of ohmic heating (OH) for pasteurization of whey based drink  (sugar: 5% litchi juice: 8%; pectin: 0.7%; Potassium meta bisulphate : 1.5%). The three OH process variables were processing time, applied  voltage and height of ohmic heater. Optimum conditions obtained by numerical optimization were processing time - 7.6 min, applied voltage – 49.5 V and thickness – 40 mm to achieve optimum conditions (maximum desirability = 0.863) with the predicted value for temperature was  73.80 o C, cell viability 20.53 X103cfu/mL, color index 54.83 and sensory score 7.55.
Keywords: Ohmic heating; Whey; Box Behnken; Response Surface Methodology